A pilot study of Enhance Recovery after Surgery (ERAS) for liver resection - Jarmin R.; Mohamad I.S.; Ahmad A.W.; Othman H.; Zuhdi Z.; Ariffin, AC (International Islamic University Malaysia, 2024)
Background: Morbidity post hepatectomy still remain persistent throughout decades compared to other surgery. Modern approach have been introduced to improve safety and reduce morbidity whilst at the same time enhance patient recovery. Thus, enhanced recovery after surgery or fast track recovery program for liver resection was initiated. Objective: The aim of this study was to achieve discharge by postoperative day 3 for minor resection and day 5 for major resection. Design and Setting: This is a prospective study conducted in Hospital Universiti Kebangsaan Malaysia (HUKM) from September 2014 till April 2015. Material and Methods: All patients undergoing open liver resection were included in the study. They were then managed post operatively according to ERAS protocol that was drawn up based on previous studies. Patient's demographics data, intra operative parameters, postoperative complications and adherence to postoperative recovery protocol were recorded. Results: Seventeen patients (7 major and 10 minor resection) were recruited. The mean length of hospital stay for minor resection was 5.9 and major resection was 9.6 .With regards to the targets, 4 out of 10 (40%)patients in minor resection group and 4 out 7 (57.1%) in the major group were discharged on time. 9 patients had postoperative complications with no mortality recorded. In terms of the ERAS protocol targets, the PCA morphine discontinuation target was achieved in 15 patients (88.3%), nasogastric tube removal (13 patients -76.5%), urinary cathether removal (6 patients - 35.3%), abdominal drains removal (9 patients-52.9%) and resumption of full diet was achieved by 82.4% (14 patients). Conclusion: From these overall achievement, most of our targets have been met and this shows that our ERAS protocol is safe to be applied to patient undergoing hepatectomy. Limitations: Some patients had achieved their target but not discharged for unknown reason.